2015
DOI: 10.1016/j.bone.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of sclerotic changes in the starting mechanisms of collapse: A histomorphometric and FEM study on the femoral head of osteonecrosis

Abstract: These results demonstrated that both shear stress and shear strain tend to be concentrated on thickened bone trabeculae at the boundary. Fracture analyses revealed that the boundary of sclerotic changes, which results from the repair process, may be the starting point of the fracture. Additionally, the osteoclastic activity increases after collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
2
35
0
2
Order By: Relevance
“…The collapse risk also depends on the stage of ONFH and the location of the necrotic lesion. Karasuyama suggested that stress concentration along the lateral sclerotic boundary triggered the subchondral fracture and finally induced the femoral head collapse. Kubo reported different collapse rates of 0%, 23%, and 81%, respectively, corresponding to different locations of lateral sclerotic boundary at the medial one‐third, the middle third, and the lateral one‐third of the weight‐bearing portion of the acetabulum, and he found that the anterior sclerotic boundary could also have an impact on the risk of collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The collapse risk also depends on the stage of ONFH and the location of the necrotic lesion. Karasuyama suggested that stress concentration along the lateral sclerotic boundary triggered the subchondral fracture and finally induced the femoral head collapse. Kubo reported different collapse rates of 0%, 23%, and 81%, respectively, corresponding to different locations of lateral sclerotic boundary at the medial one‐third, the middle third, and the lateral one‐third of the weight‐bearing portion of the acetabulum, and he found that the anterior sclerotic boundary could also have an impact on the risk of collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical structure of osteonecrotic femoral head has four layers: cartilage, osteonecrotic area, sclerotic area, and normal area. Recent studies have proposed that the decrease in structural strength is correlated with sclerotic area and osteonecrotic edge, enabling collapse prediction [16,19]. During the pathological process, collapse of the osteonecrotic femoral head occurs because of continuous spreading of trabecular fracture, which is not a sudden process, and thus the osteonecrotic area includes the collapse area and non-collapse area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, collapse must be treated surgically for femoral head osteonecrosis, and preventing collapse has been the focus of non-joint replacement therapy [6][7][8][9][10][11][12][13][14]. Current studies of collapse are typically performed from the biological, biomechanical, or mechanobiological perspective [15][16][17][18][19]; however, the mechanism of collapse is unclear, leading to insufficient effective preventive measures and unsatisfactory efficacy of hippreserving surgery. As the number of studies of miRNA in orthopedics has increased, specific miRNAs involved in femoral head osteonecrosis have been identified [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis is based on the effects of shear stress at the boundary of necrotic and normal zones [2], and the other is in accordance with the grade of bone resorption at the boundary [3]. Karasuyama et al [4] indicated that sclerotic differences at the boundary may play a crucial role in the pathomechanism of femoral head collapse. Core decompression with or without bone grafting are the most common technique for the early stages of ONFH [58].…”
Section: Introductionmentioning
confidence: 99%